2001
DOI: 10.2307/3552195
|View full text |Cite
|
Sign up to set email alerts
|

Physician Distribution and Physician Shortage Intensity in Ontario

Abstract: Au cours des années 1990, en Ontario et dans de nombreuses autres jurisdictions, le point central du débat sur les ressources humaines en médecine s'est déplacé d'un surplus généralisé à une pénurie. Cependant, le problème demeure de l'accès équitable à ces ressources et aux services de santé en général. Pendant cette période, l'effort en matière de politiques gouvernementales a été largement orienté vers ce qui a été perçu comme une "maldistribution" des ressources entre les régions géographiques. Cet article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The issue of mentorship in medical education is an emergent one, that previously took a back-seat to more pragmatic concerns such as the uneven distribution of physicians, often interpreted as a shortage. 17 Within medical education, mentoring is broadly defined as a process of extending supportive wisdom, guidance, and reflection in an informal way on the part of the mentor. It is regarded as a key component of ensuring recruitment and retention, 18 in role-modeling, 19 introducing practical training, and increasing confidence, 20 improving outcomes, 21 and encouraging trainees to take up surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of mentorship in medical education is an emergent one, that previously took a back-seat to more pragmatic concerns such as the uneven distribution of physicians, often interpreted as a shortage. 17 Within medical education, mentoring is broadly defined as a process of extending supportive wisdom, guidance, and reflection in an informal way on the part of the mentor. It is regarded as a key component of ensuring recruitment and retention, 18 in role-modeling, 19 introducing practical training, and increasing confidence, 20 improving outcomes, 21 and encouraging trainees to take up surgical training.…”
Section: Discussionmentioning
confidence: 99%
“…The “textbook” response to reduce labour or skill shortages is to raise wages and/or non‐wage benefits (such as a pension plan or a group Registered Retirement Savings Plan or RRSP[3]) or alter the working conditions to attract or retain personnel. However, employers may fail to respond to labour and skill shortages through wage and benefit mechanisms because rigidities in wages and fringe benefits coverage can occur as a result of collective bargaining agreements (Simpson, 1985), public policies (Kralj, 2001), or a reluctance to raise wages to attract new recruits to the extent that they would have to raise wages of their internal incumbents for reasons of internal equity[4] (Johansen and Strom, 2001). Haskel and Martin (1993b) further argue that skill shortages can actually reduce productivity because skill shortages tilt the composition of employment away from skilled workers towards the unskilled; they also leave the firm less able to bargain higher levels of effort from their workers. Training expenditure per employee.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that there is both a maldistribution and a shortage of physician resources in Ontario, as is the case in most of Canada (Kralj, 2001a). The current Ontario shortage is estimated to exceed 2,300 physicians (Kralj, 2001b).…”
Section: Background Information On Physicians In Ontariomentioning
confidence: 99%
“…The overall supply of physicians, their geographic distribution, and productivity is an issue of concern for both the government and individuals as it determines service availability or access. Both national and provincial reviews of the health care system in Canada have concluded that there is a shortage of health care personnel, especially physicians (Standing Senate Committee on Social Affairs, Science and Technology, 2002;McKendry, 1999;Kralj, 2001a). Evidence of impending physician shortages are also beginning to appear in the United States (Cooper et al, 2002).…”
mentioning
confidence: 99%